Vacuum-therapy in the complex treatment of gunshot wounds: current aspects and prospects (review) - Parkhomenko, Kyrylo; Tsivenko, Olexiy; Shmorhun, Volodymyr; Briukhanova, Tetiana (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. Nowadays an effective treatment of gunshot wounds is an extremely urgent problem of the health care system. Ballistic injuries occupy a leading position in the structure of combat wounds. Moreover, they are associated with purulent-infectious complications, disability, which causes a long-time healing and rehabilitation of the patients. The vacuum-therapy method is used in clinical practice for reducing the frequency and severity of complications and cuttingthe wound process’s stages duration. At the same time, there is no consensus in the scientific community regarding the feasibility of vacuum therapy application for this type of injuries. The aim of our study was to analyze scientific literature data regarding the feasibility of vacuum therapy using in the complex treatment of gunshot wounds. Materials and methods. Open sources of scientific literature were processed, in particular, but not exclusively, the results of clinical studies, data from several studies to summarize and analyze information aboutvacuum therapy effect on cytological, biochemical, hematological, morphological and other parameters in patients with gunshot wounds. Results and discussion. The data of studied papers indicate that the vacuum-associated therapy method’sapplication allows almost two times accelerationof granulation tissue formation, more effective wound cleaning from necrotic tissues and microbial contamination, thereby significantly reducing of healing period duration. The mechanisms of these effects realization are multifactorial and include reduction of edema and exudate amount, normalization of local blood flow, change of local expression of growth factors related to angiogenesis, etc. Conclusions. Based on the data presented in the scientific literature, it is possible to conclude that vacuum therapy has a significant positive effect on the course of the wound process, compared to traditional schemes for gunshot wounds therapy, which reduced the frequency of complications and allowed to cut convalescence period in patients with gunshot wounds.